AI's Revolutionary Role in Cyber Defense and Social Engineering - Muhammad Ismaeel Khan; Aftab Arif; Ali Khan (Information Technology and Science (ITScience), 2024)
Creative methods of cybersecurity are required due to the growing complexity of cyber threats, especially those originating from social engineering techniques. The revolutionary role that artificial intelligence (AI) is playing in transforming cybersecurity practices is examined in this review article. It starts by looking at social engineering assaults and how AI technologies improve the ability to identify threats and take appropriate action. The study goes on to address the particular uses of AI in a number of cybersecurity fields, such as automated incident response, fraud detection, and anomaly detection. The application of AI in cybersecurity is not without difficulties, despite its many advantages. Significant challenges are presented by problems with data quality and bias, adversarial attacks, ethical issues, and resource requirements. In order to create complete cybersecurity plans, it is crucial to integrate AI with human expertise and emphasize the necessity for human oversight and collaboration. Future developments in AI technology are expected to continue, especially in the areas of machine learning algorithms and their integration with newly developed platforms like block chain and the Internet of Things (IoT). Case studies reveal how AI has been successfully implemented in businesses in a variety of industries, demonstrating how AI may enhance danger detection and reaction times. Artificial intelligence has enormous potential to improve cybersecurity protocols. In order to secure a safer digital future, organizations that adopt AI technology while addressing ethical issues and promoting a culture of continuous learning will be in a better position to manage the always changing terrain of cyber dangers.